Finance and Development, June 2006. (Finance and Development; Finance and Development ;, 2006)
Asia Rising -- explores Asia's role in the world economy, the challenges faced from globalization, the quest for greater regional financial integration, the problem of lagging investment, and why East Asia performed so much better than Latin America. It also looks at the recovery of Japan and the rise of India and China. The economies of the ASEAN-4 come under the microscope in Country Focus. Other articles examine financial sector reform in Africa and the remaining hurdles to financial integration in the European Union. People in Economics profiles Paul Krugman, Back to Basics focuses on hedge funds, and the Straight Talk column looks at the problem of underdevelopment.